DAMPAK LINGKUNGAN ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA PETUGAS LAYANAN KESEHATAN (Studi Kasus Rumah Sakit Kota Cimahi): The Effect Of The Work Environment And Leadership Style On Employee Job Satisfaction In Hospitals In The City Of Cimahi. - Ferrari Oktavian, Rizky; Sriwardani (Sains Manajemen: Jurnal Manajemen Unsera, 2021)
This study aims to determine the effect of the work environment and leadership style on employee job satisfaction in hospitals in the city of Cimahi. This study used a descriptive verification approach, and 91 employees were sampled using multiple regression analysis assisted by SPSS 23 software. The primary data of this study were obtained from questionnaires and interviews. While secondary data is obtained through notes and publications as well as literature. The results showed that there was an influence between work environment variables and leadership style on employee job satisfaction at health service hospitals. The influence of the work environment has an influence on employee job satisfaction so that employees are committed and loyal to the organization. Meanwhile, a good leadership style can increase employee job satisfaction. This is also evidenced by the Adjusted R Square value of 0.571 or 57.1%.